A critical realist account of the factors enabling and constraining lesson differentiation in stem education: a case study of a private school in the eastern suburbs of Johannesburg - Kistoo, Kerisha (University of the Witwatersrand, Johannesburg, 2024)
In the past two decades, South Africa's democratic government has prioritised equality, stemming from its history of apartheid and colonialism. This commitment extends to the education sector, where there's a growing emphasis on inclusive education and the need for differentiation – tailoring lessons to accommodate diverse learning needs in mainstream classrooms. However, existing educational research underexplores how teachers go about planning lessons with the aim of differentiating to accommodate their learners’ needs. Recognising this gap, this study explores the enabling and constraining factors of differentiation within South Africa's context, particularly in STEM subjects. Through interviews with seven STEM teachers in a private school in Johannesburg's Eastern suburbs, the study delves into the complex interplay of social, agential, and cultural factors influencing differentiation. It draws on critical realism and social realism as supportive theories underpinning the data analysis. This study highlights that teaching is shaped by teachers’ experiences within the South African education system, which can either constrain or enable differentiation. Ultimately, this research aims to contribute to the growing knowledge on differentiation for new and existing teachers, aiming to contribute to ongoing discussions on inclusive education and pedagogical practices.
A research report Submitted in fulfillment of the requirements for a Master of Education, In the Faculty of Humanities , Wits School of Education, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Differentiation; Inclusive Education; STEM; Critical Realism; Social Realism; Agency; Teaching Training; Support; Paradigm Shifts in Education; Student-Teacher Relationship; SDG-4: Quality education